Market trends and analysis of blockchain technology in supply chain - Thakur, Anusha (Frontiers in Blockchain, 2023)
Technology is an important tool in the armory of state-of-the-art innovations, in terms of both digital expansions and disruptions. With blockchain technology gaining momentum, different industries are emphasizing experimentation with it. Nowadays, organizations are emphasizing towards agile and leaner supply chains with end-to-end prominence via the incorporation of this latest technology, thereby boosting services across the world. The revolutionary features of blockchain technology are paving the way for greater opportunities for supply chain businesses. The technology has the potential to become a supply chain data utility and repository that offers benefits to all its users, such as unique market information that would be otherwise unavailable from any other source. This paper contemplates the need for blockchain technology in the supply chain and its contribution to enhancing the overall efficiency and demand planning processes of businesses. It discusses the latest market trends and factors driving the need for the incorporation of blockchain in the supply chain sector and the future scenario. Different use cases of the technology, market challenges in the implementation of the technology, and the solutions offered by different companies to address such problems have also been discussed.